Social Cost-Benefit Analysis – A Case Study of Tata Steel Coal Washery, Jamadoba. (International Journal of Scientific Research and Management (IJSRM), 2017)
Social cost benefit analysis is an appraisal tool to evaluate a project from the view point of the society as a whole. It refers to the analysis of the costs and/or the benefits that a society may have to bear and/or get from the proposed project. It is a systematic and cohesive economic tool(method) to survey all the impacts caused by an urban development project. It is a study of feasibility of a project in terms of its total economic Cost and total economic Benefits, not just the financial effect (investment cost like tax and fees, et but all th social effects like pollution, safety indirect (labour) market, legal aspects, etc. The paper analyses the application of Social Cost Benefit Analysis on Expansion of Jamadoba Coal washery based on Mines plant and tries to highlight the social costs and benefits associated with each project. In fact, Coal continues to play a major role in the economic development of a country, especially in metallurgical industries and conventional power generation plants. Coal is the dominant energy source in India, accounting for more than half of the country’s requirements.70% of India’s coal production is used for power generation, with the remainder being used by heavy industry and public use. In a bid to break the public sector monopoly over coal, the government is seeking to introduce legislative changes allowing for private mining, whilst liberalizing norms for the allocation of captive blocks permitting trading of coal. The government is contemplating the allocation of captive blocks for setting up was here in the private sector. Captive block holders would also be permitted to sell their coal on the open market. The current legislative requirements permit private-sector investment only for the limited purpose of setting up coal washeries and captive mining for specified end-uses, including setting up power plants, fertilizer and steel units.